“THE USURPING PRINCEPS”: MAXENTIUS’ IMAGE AND ITS CONSTANTINIAN LEGACY - Sven Betjes; Sam Heijnen (Journal of Ancient History and Archaeology)
This article deals with self-representation of Maxentius, who ruled over Italy and North Africa between 306 and 312. It focuses on the imagery and language that was distributed through coins and portraits during Maxentius’ reign, as well as their reception under Constantine immediately after the Battle of the Milvian Bridge (312). It argues that Maxentius revitalized the tradition of a princeps at Rome in order to play upon sentiments of neglect felt at Rome and the time. In coinage, this was most explicitly done through the unprecedented use of the princeps title on the obverse, which initially may have caused a misunderstanding in the more distant parts of the Maxentian realm. The idea of the princeps was captivated in portraiture through visual similarities with revered emperors, especially with Trajan, and through insertion of Maxentius’ portraits in traditional togate capite velato. When Constantine defeated Maxentius in 312, he took over some of the imagery and language that had been employed by his deceased adversary. Constantine, too, presented himself as a princeps. This not only shows that Maxentius’ representational strategies had been effective, but also brings to light how Constantine managed to deal with the memory of someone who had been one of Rome’s greatest benefactors.